Professional Identity: A Qualitative Inquiry of Experienced Counsellors - Alves, Sara; Gazzola, Nicola (Canadian Journal of Counselling and Psychotherapy, 2011)
There are many recent changes to the practice of counselling and psychotherapy in Canada. Newly established statutory regulation of psychotherapy in Ontario and Quebec, and new legislation in the province of Nova Scotia protecting the title “counselling therapist,” are examples of an emerging trend in Canada that seeks to clearly define the various mental health professions. This study employed a variation of grounded theory method to investigate how counsellors experienced their professional identities. Nine experienced master’s-level counsellors in a midsized Canadian city were interviewed using a semi-structured interview protocol. The main goal was to develop an understanding of how they define themselves as professionals, with a focus on what they perceived as being the major influences on their professional identity. Eight major themes emerged, and a provisional model was proposed, consisting of three categories: (a) core of professional identity, (b) key influences on professional identity, and (c) instrumental influences on professional identity. Implications for counsellor education and counselling practice are discussed.